Evaluation of calcium alginate bead formation kinetics: an integrated analysis through light microscopy, rheology and microstructural SAXS - Posbeyikian, Andrés (2021)
Ca(II)-alginate beads are being produced for a broad spectrum of biotechnological uses. Despite the simplicity of their manufacturing process, in these highly complex arrangements, the final properties of the material strongly depend on the supramolecular scaffolding. Here we present a cost-effective automatized Optical Video Microscopy approach for in situ evaluation of the kinetics of alginate bead formation. With simple mathematic modeling of the acquired data, we obtained key parameters that reveal valuable information on the system: the time course of gel-front migration correlates with the plateau of the storage module, and total volume shrinkage is highly related to the stabilization of shear strain and shear stress at the yield point. Our results provide feasible and reproducible tools, which allow for a better interpretation of bead formation kinetics and a rapid screening technique to use while designing gelling materials with specific properties for technological applications.